Управленческий учет производственных запасов для целей калькулирования себестоимости - Кудина, О. Н.; Кудіна, О. М.; Kudina, О. (КНТУ, 2013)
В статье обоснована необходимость постановки и ведения управленческого учета для выявления объективной информации о затратах предприятия с целью достоверной калькуляции себестоимости продукции. В частности автором предложена информационная система закупочной деятельности предприятия с подробной характеристикой поведения затрат на приобретение и хранение запасов, позволяющая проводить экономически обоснованное ценообразование. У статті обґрунтовано необхідність постановки та ведення управлінського обліку для виявлення об'єктивної інформації про витрати підприємства з метою достовірної калькуляції собівартості продукції. Зокрема автором запропонована інформаційна система закупівельної діяльності підприємства з докладною характеристикою поведінки витрат на придбання і зберігання запасів, що дозволяє проводити економічно обґрунтоване ціноутворення. In the article the necessity of setting and management accounting to identify objective information about the costs of the enterprise for the purpose of accurate product costing. In particular, the author offers information system procurement company with more characteristic behavior of the cost of acquisition and storage of stocks, allowing an economically sound pricing. The article presents the specialists are able to periodically compare the costs incurred with respect to standards or pledged to the previous periods, and to use this information in the process of budgeting and strategic business planning enterprise.
Управлінський облік виробничих запасів для цілей калькулювання собівартості
Management accounting of productive reserves for the purposes of calculation of the cost
Keywords: управленческий учет; производственные запасы; затраты; калькулирование себестоимости; управлінський облік; виробничі запаси; витрати; калькулювання собівартості; management accounting; productive reserves; costs; calculation of the cost